Denmark : 2018 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2018)
This 2018 Article IV Consultation highlights that the Danish economy continues to enjoy solid growth. The output gap has seemingly closed for the first time since the global financial crisis. Unemployment is low and close to its estimated structural level with signs of labor shortages and capacity constraints in some sectors. Inflation remains subdued. Property prices in urban areas are rising swiftly and household debt remains elevated despite recent deleveraging. The increasingly binding constraints highlight Denmark's reduced growth potential, reflecting structurally weak productivity growth and the post-crisis investment slowdown. The outlook is for continued robust growth, which is projected to exceed its trend in the near term, reaching 2.0 percent in 2018 and 1.9 in 2019.